TINJAUAN YURIDIS TERHADAP PEMBERIAN KREDIT BANK DENGAN JAMINAN PERSONAL GUARANTEE (Study Pada Bank BRI Cabang KCP Willem Iskandar) - Kennie Dhillon (University of North Sumatera, 2013)
Abstract : Banks play an important role in serving the community. The process of credit with Bank BRI branch KCP Willem Alexander, among others: The entire entry will be submitted in writing by the customer / prospective borrowers who file signed by the authorized officials. Letter of request through the